Biogenic Synthesis of TiO₂ Nanoparticles Mediated by the Ethanol Extract of Avocado Peel and Its Photocatalytic Activity on the Degradation of Rhodamine B - Devi Andalusia; Surya Lubis; Muliadi Ramli; Irfan Mustafa; Cantik Oriza Siregar (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
The synthesis of TiO2 nanoparticles (TiO2 NPs) by the green approach is highly preferred due to its non-toxicity and environmentally friendly nature. In this work, TiO2 NPs were synthesized using titanium tetra isopropoxide (TTIP) and ethanol extract of avocado peel (Persea americana Mill). The ethanol extract of avocado peel (EEAP) contained secondary metabolites including: phenolics, flavonoids, alkaloids, saponins, and terpenoids. These compounds play a role as bioreductor to reduce metal ion, and as capping and stabilizing agents to control nanoparticle growth and prevent aggregation. The total phenolic content (TPC) of the EEAP estimated using the Folin-Ciocalteu method and the total flavonoid content (TFC) evaluated using a colorimetric assay that involved aluminium chloride were 79.75 mg GAE/g and 21.74 mg QE/g, respectively. The characterization of as-synthesized TiO2 NPs was carried out using Fourier Transform Infrared (FTIR) spectroscopy, X-ray powder diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDX), and UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS). The XRD patterns confirmed that the crystalline phase of TiO2 NPs was anatase and rutile with an average crystallite size of 19.27 nm. The TiO2 NPs had a spherical shape with Ti, O and C contents 84.9%, 10.24% and 4.86%, respectively. The optical band gap of TiO2 NPs was found to be 3.16 eV. The TiO2 NPs were used as photocatalyst for degradation of rhodamine B (RhB) dye in batch photoreactor. The TiO2 NPs exhibited high photocatalytic activity on degradation of RhB dye with degradation percentage up to 96.39% after 120 minutes of UV irradiation and 98.98% after 30 minutes of sunlight irradiation. The higher degradation percentage of RhB under sunlight compared to UV irradiation can be ascribed to the broad spectrum of sunlight and dye sensitization mechanism. Moreover, the obtained results confirmed that the biogenic synthesized TiO2 NPs present a promising approach for the removal of organic pollutants and could be effectively utilized in wastewater treatment processes.